2010
DOI: 10.1107/s0909049510040008
|View full text |Cite
|
Sign up to set email alerts
|

Phase-contrast X-ray imaging of the gas diffusion layer of fuel cells

Abstract: The understanding of and in situ observation of the transport and distribution of water in carbon-paper gas diffusion layers (GDLs) using non-destructive imaging techniques is critical for achieving high performance in polymer electrolyte fuel cells (PEFCs). To investigate the behavior of water in GDLs of PEFCs, phase-contrast X-ray imaging via X-ray interferometric imaging (XII) and diffraction-enhanced imaging (DEI) were performed using 35 keV X-rays. The XII technique is useful for the radiographic imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A further class of methods includes those termed Coherent Diffractive Imaging, which seek to exploit highly coherent beams to obtain coherent diffraction patterns from small samples or small regions of a sample, enabling very high-spatial resolution information to be extracted [30,31,32]. A number of these phase-contrast methods have been applied in materials micro-tomography [33,34,35,36,37,38,39]. …”
Section: Introductionmentioning
confidence: 99%
“…A further class of methods includes those termed Coherent Diffractive Imaging, which seek to exploit highly coherent beams to obtain coherent diffraction patterns from small samples or small regions of a sample, enabling very high-spatial resolution information to be extracted [30,31,32]. A number of these phase-contrast methods have been applied in materials micro-tomography [33,34,35,36,37,38,39]. …”
Section: Introductionmentioning
confidence: 99%
“…These experiments had been performed e.g. by Manke et al [2], Hartnig et al [3] or Mukaide et al [4] in 2D and Takeya et al [5], Flückiger et al [6], Krüger et al [7] or Eller et al [8] in 3D.…”
Section: Introductionmentioning
confidence: 99%
“…6) In this respect, we have demonstrated that phase contrast X-ray imaging techniques are applicable to in situ observations of water evolution processes in carbon paper for PEFCs at room temperature. 7) PEFCs are operated under moderate temperature conditions below 383 K, and the operation at a temperature as low as 233 K is required for their applications in the study of water transport. Thus, understanding of water accumulation, freezing, and melting in carbon paper GDLs is critical to achieving high-performance PEFCs.…”
mentioning
confidence: 99%
“…More details on DEI systems and the temperature-controlled measurement using the system were previously reported. 7,10,11) Figures 2(a)-2(c) show in-plane cross-sectional images of the carbon paper and ice formed at 233 K. The details of individual carbon fibers are visualized in spite of the pronounced density difference between the sample and the ice. Figures 2(d)-2(f ) show in-plane cross-sectional images of the carbon paper at 283 K, and meltwater seems to be isolated within the pores of carbon fibers.…”
mentioning
confidence: 99%